Centrifugal Pumps : Design and Application. - Lobanoff, Val S. (Elsevier Science, 1992)
Centrifugal Pumps: Design and Application.
Mechanical Seals for Refinery Service.
Keywords: Centrifugal pumps.; elektronické knihy; electronic books